Relevance of histopathological findings for predictive scoring of short-term treatment response to plasma exchange in severe ANCA-associated renal vasculitides - Hakroush, Samy; Korsten, Peter; Ströbel, Philipp; Tampe, Björn (Frontiers in Immunology, 2024)
Introduction: Rapidly progressive glomerulonephritis (RPGN) is characterized by a rapid loss of kidney function, affecting both renal and overall patient survival. Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a small vessel vasculitis affecting multiple organ systems including the kidney, and among most frequent causes of RPGN. We here aimed to validate a recently described scoring system for short-term treatment response to therapeutic plasma exchange (PLEX) in a well-characterized and independent cohort of severe renal AAV presenting with RPGN. Furthermore, we compared this scoring with established classification systems in renal AAV including histopathological findings. Methods: We here directly compare the scoring system with retrospective data about PLEX treatment in our own clinical practice and according to current recommendations in a cohort of 53 patients with severe AAV presenting with RPGN confirmed by kidney biopsy. Results: We here confirm that PLEX scoring is capable to identify patients at risk for short-term poor outcome in severe AAV presenting with RPGN (p<0.0001). Furthermore, multiple stepwise regression analysis revealed that the PLEX score without renal biopsy performed best to predict poor outcome in this patient population (p<0.0001). Conclusion: Our observations are especially relevant in the patient population of severe AAV since performing a kidney biopsy is often challenging in the setting of intensive care treatment, requirement of KRT with need for anticoagulation and bleeding risk. Therefore, validation of this scoring system would be of great clinical relevance in the treatment of patients with severe AAV presenting with RPGN.